2017
DOI: 10.1155/2017/9301017
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Severe Valgus Osteoarthritis Excellent Early Results in a 90-Year-Old Patient with a Valgus Deformity of 47°

Abstract: Grade III valgus deformity (tibiofemoral alignment > 20°) is present in only 0.5% of patients receiving total knee arthroplasty. Furthermore, cases with a valgus deformity exceeding 40° are even rarer. Since they mostly affect elderly, polymorbid patients, successful outcome means a great challenge. We report on a case of a 90-year-old patient with a valgus deformity of 47°. The patient was preoperatively restricted to a wheel chair, unable to walk, and only able to stand for a few seconds. The maximal knee fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In our study, we observed knee flexion reaching 130°, with a limited extension of 5°, whereas Ismailidis et al reported a maximal flexion of 100° and an extension deficit of 15° [ 19 ]. Utomo et al noted a limited right knee range of motion from 10° to 145° of flexion [ 20 ].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our study, we observed knee flexion reaching 130°, with a limited extension of 5°, whereas Ismailidis et al reported a maximal flexion of 100° and an extension deficit of 15° [ 19 ]. Utomo et al noted a limited right knee range of motion from 10° to 145° of flexion [ 20 ].…”
Section: Discussioncontrasting
confidence: 52%
“…While Ranawat’s classification suggests that grade-I valgus deformities are passively correctable [ 2 ], but we performed TKR for a grade-I valgus (8°) deformity in a 34-year-old male due to severe OA-related pain in the right knee. Ismailidis et al reported a TKR case of a 90-year-old female with grade III valgus arthritis, having a valgus angle of 47° [ 19 ]. A study by Utomo et al reported a 71-year-old female patient with grade III valgus (32°) arthritis who underwent TKR [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Lizaur-Utrilla et al 27 found that TKA provided pain, relief, satisfaction, and improvement in quality of life for octogenarian patients to the same level as septuagenarian patients. Ismailidis et al 28 wrote a case report of a 90-year-old patient with grade III valgus deformity undergoing TKA. After 3 months of rehabilitation, she had an improvement in quality of life and mobility.…”
Section: Patient Factors Agementioning
confidence: 99%
“…4 However, not all preoperative knees are the same, as more severe deformities may require more tissue releases and adjustments than less severely deformed knees. 5 In addition, severely deformed knees are usually a gradual occurrence and are more commonly seen in much older populations for which surgery and aftercare are already more complicated due to a likely increased number of comorbidities. 5 Therefore, to better achieve optimal surgical outcomes in these more complicated patients, major efforts have been made in advancing guidance-based systems, such as the robotic-assisted TKA device.…”
mentioning
confidence: 99%